Osteoid Osteoma with a Multicentric Nidus: Interstitial Laser Ablation under MRI Guidance - David Kaul; Oriane Bonhomme; Phillip Schwabe; Bernhard Gebauer; Florian Streitparth (Case Reports in Orthopedics)
Osteoid osteoma (OO) is a common benign tumor of the bone and is typically treated by thermal ablation with computed tomography (CT) guidance. Only a few cases of multicentric OO have been described. We here report the case of an 11-year-old boy with multicentric OO of the right femur treated with laser ablation under open high-field MRI guidance. The steps of the interventional MRI procedure are described, discussing the benefits and disadvantages of MRI versus CT guidance especially with regard to younger patients.